Complement or substitute? The internet as an advertising channel, evidence on advertisers on the Italian market, 2005-2009 - Marco Gambaro; Riccardo Puglisi (International Telecommunications Society (ITS), 2013)
During the last decade the internet has been the fastest growing segment in advertising. Exploiting Nielsen data, we analyze the advertising pattern displayed by the population of organizations (i.e. companies, non-profit institutions and public entities) that were active on the Italian national market during the period 2005-2009. Some reduced form evidence shows that - during this time period - smaller firms increased their ads investment on newspapers, magazines cinema comparatively more than larger firms. Radio and the internet display an opposite pattern, whereas are larger firms increasing their expenses more than smaller firms. In the lack of firmspecific output data, we also estimate a homothetic advertising cost function for different subsets of the sample. We find that media segments are (loose) substitutes, in that the estimated cross-price elasticities are positive but decidedly less than one.
Keywords: L2; L82; L86; 330; Advertising; Internet; Media Substitution